PANDANGAN DAN SIKAP MASYARAKAT TERHADAP PLULARITAS AGAMA DI INDONESIA - Sarjuni, Sarjuni (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2013)
AbstractThis article is the result of fundamental  research conducted  in 2011. It is intended to see how far the ideas of pluralism can be understood and accepted by public who are often involved in violance on the behalf of religion.The method applied in this research is indepth interview, news paper documentation, discourse analysis.Based on the analysis result, it is found that  there are three opinions about religious pluralism. First, formalitistic tradisionalist opinion, that is: there is only one true religion, it is the religion that he/she belongs to. second, the unconcerned attitude or apathy to the religious reality of religion in Indonesia.. Third, a radical opinion, they think that the followers of other religion –out side of the religion that they belong to, must be have enough, and if it is needed by using violance and force.Keyword:  pluralitas, kekerasan, konflik agama